Communicating identities among “others”: experiences of Indonesian graduate students - Latiffah Pawanteh, (Pusat Pengajian Media dan Komunikasi, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2015)
One of the features of today’s globalised living is multiculturalism and the growing internationalization of education that has resulted in greater movements of student population across various cultural boundaries. Most sojourner studies tend to focus on the experiences of immigrants, refugees, and the business communities while the experiences of the growing number of international students have been downplayed. Economic conditions and political situations in the late 1990’s have created educational opportunities for many developing countries including Malaysia. There was an increase in the number of students from developing countries with collectivist cultures studying in more similar cultural environments. Malaysia is the 12th most popular educational destination. It has been assumed theoretically that similarities in the cultural framework between the host culture and that of the international students will allow for a comfortable and more natural adaptation process. However, it is during sojourn that these students claim cultural group membership in the local context. It is here that the cultural identities of a group are negotiated, reinforced and challenged through everyday communication practices. This paper presents focus group findings with 30 Indonesian graduate students that explore their daily living experiences in an effort to unravel their process of enacting and engaging their identities through daily communication. Through their issues, challenges, and strategies for learning, living and adapting in a presumably similar cultural setting, this paper presents an account of their adaptation that reveal the unpacking of labels and norms that distinguishes them from the locals and affirms their cultural identity as Indonesians.